2014
DOI: 10.1080/1536710x.2014.961116
|View full text |Cite
|
Sign up to set email alerts
|

Walking a Tightrope: Case Management Services and Outpatient Commitment

Abstract: Effective case managers in community mental health are successful at forging a working alliance with recipients. This article explores one key aspect of case management practice, serving involuntary clients, specifically those on outpatient commitment orders. In 19 intensive interviews, a subset of a larger study, case managers shared their perceptions of the utility of outpatient commitment with a focus on how such orders impacted the professional relationship. We argue that the use of advance psychiatric dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The findings from two published articles were combined because they reported results from the same study (14,15). Twelve articles published in academic journals (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and two governmentsponsored reviews from Ontario, Canada (27,28), included in this review are listed in Table 1. Together these 14 studies incorporated the views of more than 700 participants from six countries.…”
Section: Search Resultsmentioning
confidence: 99%
“…The findings from two published articles were combined because they reported results from the same study (14,15). Twelve articles published in academic journals (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26) and two governmentsponsored reviews from Ontario, Canada (27,28), included in this review are listed in Table 1. Together these 14 studies incorporated the views of more than 700 participants from six countries.…”
Section: Search Resultsmentioning
confidence: 99%
“…Mental health workers’ stated CTO goals and conditions should complement care and treatment goals set out in the care plan [30], though workers also expressed scepticism and concern that CTOs could undermine the process of developing consumer led goals [50]. Given these challenges, Brophy and McDermott [24] recommend mental health professionals’ working with consumers on CTOs have advanced clinical and interpersonal skills.…”
Section: Core Components Of Case Managementmentioning
confidence: 99%
“…To address this, Lawn et al highlight the importance of worker empathy in engaging consumers on CTOs and the need for workers to consider ‘the relationship between what is done and how it is done’ (p. 15) [45]. Interestingly in another study, those workers who viewed CTOs as primarily coercive also reported discomfort in working with consumers on CTOs [50]. …”
Section: Core Components Of Case Managementmentioning
confidence: 99%
See 2 more Smart Citations